Economic policy uncertainty and corporate investment : The moderating effect of corporate social responsibility - Qiujin, Zhao; Salawati, Sahari (LLC “Consulting Publishing Company “Business Perspectives”, 2025)
Economic policy uncertainty has a profound impact on firms’ investment decisions, mainly in terms of increased risk and uncertainty for firms when planning future investments. This study aims to explore the impact of corporate economic policy uncertainty on corporate investment, as well as how corporate social responsibility disclosure moderates the relationship between economic policy uncertainty (EPU) and corporate investment. The analysis uses a sample of Chinese listed companies from 2010 to 2022, including 33,791 observations. The study uses ordinary least squares (OLS) regression with clustered standard errors. The basic and robust regression empirical results show that economic policy uncertainty has a negative impact on corporate investment. However, corporate social responsibility plays an important moderating role between them. The two-stage least squares method (2SLS) is used to solve the endogeneity problem of reverse causation. The heterogeneity results show that economic policy uncertainty significantly dampens business investment, while corporate social responsibility (CSR) is effective in mitigating this negative effect, especially among non-state-owned and low-cash-flow firms, where this moderating effect is more pronounced. The study concludes that as corporate social responsibility disclosure enhances information transparency and investor confidence, companies should prioritize CSR programs that ultimately help companies remain competitive and attractive to investors in volatile markets. Meanwhile, this also highlights the strategic importance of CSR in mitigating external risks, such as those presented through volatile economic policies.